1996
DOI: 10.1073/pnas.93.22.12605
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of two somatostatin variants in the frog brain: characterization of the cDNAs, distribution of the mRNAs, and receptor-binding affinities of the peptides.

Abstract: In tetrapods, only one gene encoding a somatostatin precursor has been identified so far. The present study reports the characterization of the cDNA clones that encode two distinct somatostatin precursors in the brain ofthe frog Rana ridibunda. The cDNAs were isolated by using degenerate oligonucleotides based on the sequence of the central region of somatostatin to screen a frog brain cDNA library. One of the cDNAs encodes a 115-amino acid protein (prepro-somatostatin-14; PSS1) that exhibits a high degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
107
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 41 publications
7
107
1
Order By: Relevance
“…The cDNA encoding its precursor (PSS2) was characterized soon thereafter (Tostivint et al 1996). An ortholog of the frog SS2 gene has been subsequently revealed by cDNA cloning in goldfish (Carassius auratus; Lin et al 1999b), West African lungfish (Protopterus annectens; Trabucchi et al 1999), white sturgeon (Acipenser transmontanus; Trabucchi et al 2002), and chicken (Gallus gallus; Trabucchi et al 2003).…”
Section: Ss2/cortistatinmentioning
confidence: 99%
“…The cDNA encoding its precursor (PSS2) was characterized soon thereafter (Tostivint et al 1996). An ortholog of the frog SS2 gene has been subsequently revealed by cDNA cloning in goldfish (Carassius auratus; Lin et al 1999b), West African lungfish (Protopterus annectens; Trabucchi et al 1999), white sturgeon (Acipenser transmontanus; Trabucchi et al 2002), and chicken (Gallus gallus; Trabucchi et al 2003).…”
Section: Ss2/cortistatinmentioning
confidence: 99%
“…It should be noted however that, apart from their C-terminal region, PCST and PSS2 possess very little sequence similarity. In addition, their distributions in the brain are relatively different: while the SS2 gene is expressed in various subdivisions of the brain in all species studied so far (Tostivint et al 1996, Lin et al 1999, Trabucchi et al 1999, 2003, the CST gene is almost exclusively expressed in the telencephalon (de Lecea et al 1996(de Lecea et al , 1997a(de Lecea et al , 1997b. Although the parentage between the PSS2 gene and the PCST gene is supported by phylogenetic analysis (Trabucchi et al 1999, 2003, Devos et al 2002, the orthology of the two genes has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to prepro-SS1 (PSS1), a second somatostatin precursor, encoded by a distinct gene, has been characterized in several representative species, including sturgeon (Trabucchi et al 2002), goldfish (also named PSSIII; Lin et al 1999), zebrafish (also named PSS3; Devos et al 2002), lungfish (Trabucchi et al 1999), frog (Tostivint et al 1996), chicken (Trabucchi et al 2003), mouse (de Lecea et al 1997a), rat (de Lecea et al 1996) and human (de Lecea et al 1997a, Fukusumi et al 1997. Peptides derived from this second precursor (named SS2 in non-mammalian species and cortistatin (CST) in mammals) exhibit a more variable structure than SS1 (Spier & de Lecea 2000, Tostivint et al 2004 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The somatostatin 1 (SS1) gene has been cloned from all vertebrate classes from agnathans to mammals (Conlon et al, 1997;Lin et al, 1998;Tostivint et al, 2004). Somatostatin 2 (SS2), the duplicated gene of SS1 by a segment/chromosome duplication, has been characterized in numerous vertebrates, including frog (Vaudry et al, 1992;Tostivint et al, 1996), rat (de Lecea et al, 1996), human (de Lecea et al, 1997;Fukusumi et al, 1997), mouse (de Lecea et al, 1997), chicken (Trabucchi et al, 2003), lungfish (Trabucchi et al, 1999), goldfish (Lin et al, 1999), white sturgeon (Trabucchi et al, 2002), grouper (Ye et al,20 05), zebrafish (GenBank accession No. BG307388), opossum ((DS)ENSMODG00000002663), and pufferfish (GenBank accession No.…”
Section: Introductionmentioning
confidence: 99%